Is there is a role for laparoscopy for treatment of appendicular mass? - Mohammed, Asem F.; Shaheen, Mahmoud A.; Eldesouky, Mahmoud S. (International Surgery Journal, 2018)
Background: The surgical intervention for acute appendicitis presenting with appendicular mass is not well established. The aim of this study was to evaluate the benefits of early laparoscopy and laparoscopic appendectomy (LA) in the treatment of appendicular mass. Methods: During a 1-year period, 48 patients underwent LA for suspected appendicitis (n = 39), generalized peritonitis (n = 1), and an appendicular mass (n = 8). Results: All appendectomies were attempted and done laparoscopically except in one case (appendicular abscess), converted to an open approach. None of appendicular mass patients developed complications. There were no deaths. There was no significant difference between appendicular mass forming patients and non-mass-forming patients who underwent LA for an early appendicular mass as regard to the operative time (median [interquartile range]: 50 [36–60] vs 45 [25–50] min, p = 0.085) and postoperative hospital stay (median [interquartile range]: 2 [1–2] vs [1–2] days, p = 0.1). Conclusions: Early LA for appendicular mass patients is feasible, safe, and avoids misdiagnoses and the need for hospital readmission.